Characterization of Indigenous Lactic Acid Bacteria (LAB) from the wild horse milk of Bima - Narda Widiada (Health Notions, 2018)
The wild horse milk are milk result of pressing out from laktasi horse which its wild life in free nature. The horse milk do not destroy during depository at room temperature. In the wild horse milk of Bima have been identified six species indigenous Lactic Acid Bacteria (LAB) (Widiada, 2006). The aims of the research is to know characteristic from indigenous Lactic Acid Bacteria result of isolation from wild horse milk of Bima. Examination of characteristic are done by fenotifik characterization. The result of research showed that species indigenous Lactic Acid Bacteria pertained LAB species with homofermentatif ferment pattern. The LAB species can grow goodness at temperature 37oC, media with NaCl 3,5% and 6,5% and also can grow at low pH (pH 4,5) and high pH (pH 9,6), except Lc. lactis subsp lactis do not grow at pH 9,6.